A method for preparing an adsorbent for pressure swing adsorption with a microporous structure

By using a combination of microporous alumina spheres and aminosilanes, an efficient and low-cost adsorbent was prepared, which solved the problem of high cost of preparation of adsorbents in the prior art and achieved efficient carbon dioxide adsorption effect.

CN117920161BActive Publication Date: 2025-02-07SHANGHAI YUJIE CATALYST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410187242.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-20
Publication Date
2025-02-07
Estimated Expiration
2044-02-20

AI Technical Summary

Technical Problem

In the prior art, the production cost of pressure-switching adsorbents used to adsorb carbon dioxide is high and is not suitable for large-scale industrial applications.

Method used

Alumina spheres with microporous structures are used as the adsorbent body, and an adsorbent with a large specific surface area and a rich pore structure is prepared by impregnation and curing with aminosilane.

Benefits of technology

The adsorbent for pressure-switching adsorption of microporous structures with low cost and high efficiency is realized, providing more adsorption sites and channels, and improving the adsorption selectivity of carbon dioxide.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a method for preparing an adsorbent for pressure swing adsorption with a microporous structure, which belongs to the technical field of waste gas adsorption materials, and comprises the following steps: a template agent and an alumina precursor are mixed in a mass ratio of 30 to 40:100 to form a sphere, and a porous alumina sphere is obtained by heat treatment; aminosilane is dissolved in a solvent, impregnated with the alumina sphere, and the alumina sphere is filtered out and dried and cured to obtain the alumina sphere. The alumina sphere of the present invention has a large specific surface area and a rich pore structure, can provide more adsorption sites and channels, is conducive to the diffusion and adsorption of carbon dioxide molecules on the surface of the adsorbent, and the solidified amino group can enhance the interaction between the adsorbent and carbon dioxide, and improve the adsorption selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing an adsorbent for pressure swing adsorption with a microporous structure, belonging to the technical field of waste gas adsorption materials. Background Art

[0002] In many industrial environments, it is necessary to adsorb carbon dioxide from exhaust gas to reduce emissions to the atmosphere and meet environmental regulations. For example, the adsorption of carbon dioxide from exhaust gas from coal-fired, gas-fired or oil-fired power plants can help reduce greenhouse gas emissions and meet environmental protection requirements. Many chemical plants adsorb carbon dioxide from exhaust gas to reduce emissions to the atmosphere and reduce the carbon footprint of chemical plants. Adsorbing carbon dioxide from exhaust gas can not only reduce the impact on the environment, but also save energy and resources for enterprises and achieve sustainable development. After the carbon dioxide adsorbed on the adsorbent is released through desorption, a relatively pure carbon dioxide can be obtained, which has a wide range of applications.

[0003] At present, some pressure swing adsorbents for carbon dioxide adsorption have been developed, such as MOF-177 metal organic framework, which can adsorb carbon dioxide with high selectivity. However, the synthesis and preparation costs of MOF materials are relatively high, which is not conducive to large-scale industrial application. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a method for preparing an adsorbent for pressure swing adsorption with a microporous structure having a low preparation cost and high efficiency.

[0005] The technical solution adopted by the present invention to solve the technical problem is: a method for preparing an adsorbent for pressure swing adsorption with a microporous structure, characterized in that it comprises the following steps:

[0006] 1) The template agent and the alumina precursor are mixed in a mass ratio of 30-40:100 to form a sphere, and a porous alumina sphere is obtained by heat treatment;

[0007] 2) Dissolve the aminosilane in a solvent, impregnate it with alumina balls, filter out the alumina balls, and then dry and solidify them to obtain the product.

[0008] The alumina ball of the present invention has a large specific surface area and a rich pore structure, which can provide more adsorption sites and channels, and is conducive to the diffusion and adsorption of carbon dioxide molecules on the surface of the adsorbent. The solidified amino group can enhance the interaction between the adsorbent and carbon dioxide and improve the adsorption selectivity.

[0009] Preferably, in the above preparation method, the template described in step 1) is a composite template of polystyrene and polyacrylic acid in a mass ratio of 30-45:55-70. Polystyrene has good solubility and can be mixed with an alumina precursor to form a mixed system. Polyacrylic acid, as a dispersant and stabilizer, can help polystyrene to be evenly dispersed in the alumina precursor, further promoting the formation of pores. The pore size and pore structure of the alumina spheres are controlled by adjusting the ratio and treatment conditions of polystyrene and polyacrylic acid. At the same time, the addition of polyacrylic acid can change the surface charge of the alumina spheres, affecting the formation of pores and the distribution of pore structures. The mixed system of polystyrene and alumina precursors can form a relatively stable emulsion or colloid, which is beneficial to the stability of the molding process. Polyacrylic acid, as a dispersant and stabilizer, can increase the viscosity and dispersibility of the system, prevent the precipitation and aggregation of particles, thereby improving the stability of molding. It is easy to remove by heat treatment, leaving alumina spheres with hollow structures or porous structures, which is relatively simple.

[0010] Preferably, in the above preparation method, the alumina precursor in step 1) is γ-Al2O3 nanopowder, and the γ-Al2O3 nanopowder is fibrous. Using fibrous γ-Al2O3 nanopowder as an alumina precursor is conducive to forming a continuous pore structure, which can provide more adsorption sites and channels, and is conducive to the diffusion and adsorption of carbon dioxide and the like in the porous alumina sphere.

[0011] Preferably, in the above preparation method, the mixing in step 1) is: first dry-mix the template and the alumina precursor, and then add 3% to 5.5% of water by mass of the template to mix after mixing evenly, and use a rolling ball machine to form spheres with a particle size of 2mm to 5mm after mixing evenly. Adding a small amount of water to the mixture of the template and the alumina precursor can not only promote adhesion during ball formation, but also this part of water can be slowly vaporized during the drying process, leaving microchannels for the spheres. These microchannels serve as volatilization channels for the template during the heat treatment process, which can effectively prevent explosion and improve the forming rate.

[0012] Preferably, in the above preparation method, the heat treatment in step 1) is: drying the sphere and then calcining it at a temperature of 305°C to 310°C. The two components of the composite template selected in the present invention have similar thermal decomposition temperatures. The preferred calcination temperature can separate the two components from the sphere at an appropriate rate, thereby ensuring the molding rate.

[0013] Preferably, in the above preparation method, the drying temperature is 70°C to 80°C. The heating rate of the roasting from room temperature to the roasting temperature is 25°C / h to 30°C / h. The vaporization rate of water is controlled by the drying rate, and microchannels are reserved for the sphere while preventing cracks, thereby increasing the forming rate while ensuring the strength of the sphere as much as possible. The heating rate is controlled during roasting. As the temperature increases, the strength of the alumina sphere will gradually increase. The roasting process should reduce thermal expansion before the alumina sphere has sufficient strength. The preferred heating rate can effectively reduce the bursting of the sphere caused by thermal expansion of different materials.

[0014] Preferably, in the above preparation method, the aminosilane described in step 2) is N-(2-aminoethyl-3-aminopropyl)trimethoxysilane or 3-aminopropyltrimethoxysilane. After the preferred aminosilane is cured in the pores of the alumina ball, the selectivity for carbon dioxide adsorption can be better enhanced. More preferably, the aminosilane is N-(2-aminoethyl-3-aminopropyl)trimethoxysilane. N-(2-aminoethyl-3-aminopropyl)trimethoxysilane is not only firmly and stably cured with the alumina ball, but also contains two amino groups, aminoethyl and aminopropyl. After curing, the amino density is higher, and the saturation during the adsorption of carbon dioxide is greater.

[0015] Preferably, in the above preparation method, the solvent in step 2) is methanol, ethanol or dimethylformamide (DMF). More preferably, the solvent is DMF. Ethanol and methanol have good solubility for most aminosilanes and are easy to obtain and handle. DMF has good solubility for aminosilanes and can provide higher solubility and dissolution rate.

[0016] Preferably, in the above preparation method, the immersion in step 2) is to immerse the alumina balls in an aminosilane solution for 18 to 24 hours, and the mass concentration of the aminosilane solution is 50% to 60%. The preferred mass concentration of the aminosilane solution ensures good fluidity and wettability of the solution and sufficient amino group attachment density on the alumina balls.

[0017] Preferably, in the above preparation method, the curing treatment in step 2) adopts a thermal curing method: the impregnated alumina balls are baked at 50°C to 80°C, and the baking time is controlled to be 5h to 6h. Under the preferred curing temperature and time, the curing rate can be guaranteed as much as possible while avoiding excessive temperature causing thermal decomposition of the material or other adverse effects.

[0018] Compared with the prior art, the preparation method of a microporous structure adsorbent for pressure swing adsorption of the present invention has the following beneficial effects: the present invention uses alumina balls with a microporous structure as the main body of the adsorbent, and after impregnation and curing with aminosilane, an adsorbent for adsorbing carbon dioxide is obtained. The alumina balls prepared by heat treatment of the present invention have a large specific surface area and a rich pore structure, which can provide more adsorption sites and channels, which is conducive to the diffusion and adsorption of carbon dioxide molecules on the surface of the adsorbent. Alumina is selected as the main body, which has good chemical stability and can maintain high adsorption performance in long-term use under various environmental conditions. The cured amino group has a pair of lone pairs of electrons, which can enhance the interaction between the adsorbent and carbon dioxide and improve the adsorption selectivity.

[0019] When using this adsorbent, other acid gases in the gas to be treated should be removed by other equipment as much as possible before adsorption. DETAILED DESCRIPTION

[0020] The present invention is described in detail below by way of examples. Unless otherwise specified, all raw materials used are commercially available.

[0021] Example 1

[0022] 1) Polystyrene and polyacrylic acid are prefabricated into a composite template in a mass ratio of 38:62, and the composite template is dry-mixed with fibrous γ-Al2O3 nanopowder in a mass ratio of 35:100. After mixing evenly, 4.5% water by mass of the composite template is added to mix. After mixing evenly, spheres with a particle size of 2 mm to 5 mm are formed using a rolling ball machine; the spheres are dried at 75°C and then calcined to obtain alumina spheres with a porous structure. The calcination temperature is 305°C, and the heating rate from room temperature to the calcination temperature is 25°C / h.

[0023] 2) Dissolve N-(2-aminoethyl-3-aminopropyl)trimethoxysilane in DMF to prepare an impregnation solution with a mass concentration of 55%, soak the obtained alumina balls in the impregnation solution for 20 hours, filter out the alumina balls, and bake and solidify them at 80°C for 5.5 hours.

[0024] Example 2

[0025] 11) Polystyrene and polyacrylic acid are prefabricated into a composite template in a mass ratio of 35:65, and the composite template is dry-mixed with fibrous γ-Al2O3 nanopowder in a mass ratio of 33:100. After mixing evenly, 3.5% water by mass of the composite template is added to mix, and after mixing evenly, spheres with a particle size of 2 mm to 5 mm are formed using a rolling ball machine; the spheres are dried at 75°C and then calcined to obtain alumina spheres with a porous structure. The calcination temperature is 310°C, and the heating rate from room temperature to the calcination temperature is 30°C / h.

[0026] 2) Dissolve N-(2-aminoethyl-3-aminopropyl)trimethoxysilane in DMF to prepare an impregnation solution with a mass concentration of 55%, soak the obtained alumina balls in the impregnation solution for 22 hours, filter out the alumina balls, and bake and solidify them at 80°C for 5.5 hours.

[0027] Example 3

[0028] 1) Polystyrene and polyacrylic acid are prefabricated into a composite template in a mass ratio of 40:60, and the composite template is dry-mixed with fibrous γ-Al2O3 nanopowder in a mass ratio of 38:100. After mixing evenly, 4.5% water by mass of the composite template is added to mix. After mixing evenly, spheres with a particle size of 2 mm to 5 mm are formed using a rolling ball machine. The spheres are dried at 75°C and then calcined to obtain alumina spheres with a porous structure. The calcination temperature is 305°C, and the heating rate from room temperature to the calcination temperature is 28.

[0029] 2) Dissolve N-(2-aminoethyl-3-aminopropyl)trimethoxysilane in DMF to prepare an impregnation solution with a mass concentration of 55%, soak the obtained alumina balls in the impregnation solution for 20 hours, filter out the alumina balls, and bake and solidify them at 80°C for 5.5 hours.

[0030] Example 4

[0031] 1) Polystyrene and polyacrylic acid are prefabricated into a composite template in a mass ratio of 30:70, and the composite template is dry-mixed with fibrous γ-Al2O3 nanopowder in a mass ratio of 30:100. After mixing evenly, 5.5% water by mass of the composite template is added to mix, and after mixing evenly, spheres with a particle size of 2 mm are formed using a rolling ball machine; the spheres are dried at 70°C and then calcined to obtain alumina spheres with a porous structure, the calcination temperature is 305°C, and the heating rate from room temperature to the calcination temperature is 25°C / h.

[0032] 2) Dissolve N-(2-aminoethyl-3-aminopropyl)trimethoxysilane in methanol to prepare an impregnation solution with a mass concentration of 50%, soak the obtained alumina balls in the impregnation solution for 24 hours, filter out the alumina balls, and bake and solidify them at 50°C for 5 hours.

[0033] Example 5

[0034] 1) Polystyrene and polyacrylic acid are prefabricated into a composite template in a mass ratio of 45:55, and the composite template is dry-mixed with fibrous γ-Al2O3 nanopowder in a mass ratio of 40:100. After mixing evenly, 3% water by mass of the composite template is added to mix, and after mixing evenly, spheres with a particle size of 5 mm are formed using a rolling ball machine; the spheres are dried at 80°C and then calcined to obtain alumina spheres with a porous structure, the calcination temperature is 310°C, and the heating rate from room temperature to the calcination temperature is 30°C / h.

[0035] 2) Dissolve N-(2-aminoethyl-3-aminopropyl)trimethoxysilane in ethanol to prepare an impregnation solution with a mass concentration of 60%, soak the obtained alumina balls in the impregnation solution for 18 hours, filter out the alumina balls, and bake and solidify them at 65°C for 5 hours.

[0036] Example 6

[0037] 1) Polystyrene and fibrous γ-Al2O3 nanopowder are dry-mixed in a mass ratio of 35:100, and then 3.5% of water by mass of the composite template is added to mix after mixing evenly. After mixing evenly, spheres with a particle size of 2mm~5mm are formed using a rolling ball machine; the spheres are dried at 75°C and then calcined to obtain alumina balls with a porous structure. The calcination temperature is 305°C, and the heating rate from room temperature to the calcination temperature is 25°C / hh.

[0038] 2) Dissolve N-(2-aminoethyl-3-aminopropyl)trimethoxysilane in DMF to prepare an impregnation solution with a mass concentration of 55%, soak the obtained alumina balls in the impregnation solution for 20 hours, filter out the alumina balls, and bake and solidify them at 80°C for 6 hours.

[0039] Example 7

[0040] 1) Polystyrene and polyacrylic acid are prefabricated into a composite template in a mass ratio of 38:62, and the composite template is dry-mixed with fibrous γ-Al2O3 nanopowder in a mass ratio of 35:100. After mixing evenly, 4.5% water by mass of the composite template is added to mix. After mixing evenly, spheres with a particle size of 2 mm to 5 mm are formed using a rolling ball machine; the spheres are dried at 75°C and then calcined to obtain alumina spheres with a porous structure. The calcination temperature is 305°C, and the heating rate from room temperature to the calcination temperature is 25°C / h.

[0041] 2) Dissolve 3-aminopropyltrimethoxysilane in ethanol to prepare an impregnation solution with a mass concentration of 55%, soak the obtained alumina balls in the impregnation solution for 20 hours, filter out the alumina balls, and bake and solidify them at 60°C for 5 hours.

[0042] Samples (d is 1.6 mm to 2.5 mm) were taken from the molecular sieves prepared in the examples as samples and some performance tests were performed according to GBT13550-2015.

[0043] CO2 adsorption rate: Prepare a mixed gas of CO2 and N2 at a volume ratio of 3:7, and add 1m 3 The mixed gas is passed through an adsorption column with a cross-section of 20 cm×20 cm and a length of 50 cm filled with the adsorbent obtained in the example, and the CO2 loss rate is measured.

[0044] The experimental results are shown in Table 1.

[0045] Table 1 Experimental results

[0046] .

[0047] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a microporous structured pressure swing adsorption adsorbent, characterized in that: The following steps are involved: 1) The template agent and the alumina precursor are mixed in a mass ratio of 30-40:100 to form a sphere, and a porous alumina sphere is obtained by heat treatment; 2) dissolving aminosilane in a solvent, impregnating the alumina balls, filtering out the alumina balls, and then drying and curing the alumina balls to obtain the product; The template described in step 1) is a composite template of polystyrene and polyacrylic acid in a mass ratio of 30~45:55~70; the alumina precursor described in step 1) is γ-Al2O3 nanopowder, and the γ-Al2O3 nanopowder is fibrous; the heat treatment described in step 1) is: drying the sphere and then calcining it, and the calcination temperature is 305℃~310℃.

2. The method for preparing a microporous structure pressure swing adsorption adsorbent according to claim 1, characterized in that: The mixing in step 1) is as follows: firstly dry-mix the template and the alumina precursor, and then add 3% to 5.5% of water by mass of the template to mix after the mixture is uniformly mixed, and then use a rolling ball machine to form spheres with a particle size of 2 mm to 5 mm.

3. The method for preparing a microporous structure pressure swing adsorption adsorbent according to claim 1, characterized in that: The drying temperature is 70°C to 80°C, and the heating rate of the roasting from room temperature to the roasting temperature is 25°C / h to 30°C / h.

4. The method for preparing a microporous structure pressure swing adsorption adsorbent according to claim 1, characterized in that: The aminosilane described in step 2) is N-(2-aminoethyl-3-aminopropyl)trimethoxysilane.

5. The method for preparing a microporous structure pressure swing adsorption adsorbent according to claim 1, characterized in that: The solvent in step 2) is methanol, ethanol or DMF dimethylformamide.

6. The method for preparing a microporous structure pressure swing adsorption adsorbent according to claim 1, characterized in that: The impregnation in step 2) is to immerse the alumina balls in an aminosilane solution for 18 h to 24 h, wherein the mass concentration of the aminosilane solution is 50% to 60%.

7. The method for preparing a microporous structure pressure swing adsorption adsorbent according to claim 1, characterized in that: The curing treatment described in step 2) adopts a thermal curing method: the impregnated alumina balls are baked at 50°C~80°C, and the baking time is controlled to be 5h~6h.

Citation Information

Patent Citations

  • Alumina carrier with composite pore structure and preparation method thereof

    CN102614934A

  • Carbon dioxide solid adsorbent and preparation method and application thereof

    CN109589935A